The Good Samaritan and his genes - audio/video lecture - Rolston, Holmes, 1932-2025, speaker (Colorado State University. Libraries, 2002)
This is a lecture given by Holmes Rolston at a conference on Biology and Morality at Calvin College in Grand Rapids, Michigan on November 9, 2002.

The Good Samaritan helping non-genetically related other does not fit well into a Darwinian framework. The Good Samaritan--some biologists claim--is constitutionally (=genetically) unable to act for the victim's sake. There must be a self-interested account; the Samaritan, deceived about his motives, is rewarded with reproductively profitable reputation. But such behavior, praised and imitated, jumps genetic lines and there is no differential survival advantage.
This was originally an audio recording to which some video slides were added.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Good Samaritan; selfishness; altruism; self-deception; genetics; Darwinism; reputation; religion; survival advantage